HIGH-PRESSURE MINERAL ASSEMBLAGE IN GRANITIC ROCKS FROM CONTINENTAL UNITS, ALPINE CORSICA, FRANCE - Malasoma A.; Marroni M.; Musumeci G.; Pandolfi L. (My University, 2006)
The Popolasca-Francardo area of northern Corsica contains an assemblage of continental tectonic units affected by an Alpine deformation. In one of these units, Unit 11, previously regarded as weakly metamorphosed, a metamorphic mineral assemblage characterized by sodic amphibole, phengite, quartz, albite and epidote has been found in an aplite dyke that cuts the dominant granitoids. Peak-metamorphic temperature and pressure conditions of 300-370°C and 0.50-0.80 GPa, respectively, have been determined. This finding indicates that a continuous belt of continental slices, characterized by high-pressure, low-temperature metamorphism of Tertiary age, extends from the Tenda Massif in the north to the Corte area in the south thus placing additional constraints on the tectonic evolution of Alpine Corsica. Copyright © 2005 John Wiley & Sons, Ltd.
Keywords: ALPINE CORSICA; CONTINENTAL TECTONIC UNITS; DEFORMATION; HIGH-PRESSURE/LOW-TEMPERATURE METAMORPHISM